Beyond the witch trials: Witchcraft and magic in Enlightenment Europe - Davies, Owen (2004)
Beyond the witch trials provides an important collection of essays on the nature of witchcraft and magic in European society during the Enlightenment. The book is innovative not only because it pushes forward the study of witchcraft into the eighteenth century, but because it provides the reader with a challenging variety of different approaches and sources of information. The essays, which cover England, Netherlands, Spain, Italy, Germany, Scotland, Finland and Sweden, examine the experience of and attitudes towards witchcraft from both above and below. While they demonstrate the continued widespread fear of witches amongst the masses, they also provide a corrective to the notion that intellectual society lost interest in the question of witchcraft. While witchcraft prosecutions were comparatively rare by the mid-eighteenth century, the intellectual debate did no disappear; it either became more private or refocused on such issues as possession. The contributors come from different academic disciplines, and by borrowing from literary theory, archaeology and folklore they move beyond the usual historical perspectives and sources. They emphasise the importance of studying such themes as the aftermath of witch trials, the continued role of cunning-folk in society, and the nature of the witchcraft discourse in different social contexts. This book will be essential reading for those interested in the decline of the European witch trials and the continued importance of witchcraft and magic during the Enlightenment. More generally it will appeal to those with a lively interest in the cultural history of the late seventeenth and eighteenth centuries. This is the first of a two-volume set of books looking at the phenomenon of witchcraft, magic and the occult in Europe since the ...